Meningkatkan Kreativitas Pembelajaran bagi Guru Agama Kristen di Indonesia - Jannes Eduard Sirait (DIDAKTIKOS: Jurnal Pendidikan Agama Kristen Duta Harapan, 2021)
Christian religious teachers must have good aptitude and non-aptitude skills as well as good learning creativity. Christian religious teachers in their duties are obliged to organize, guide, guide and create a healthy and fun learning environment for students. Including coaching, shaping and helping students achieve their learning achievements. To achieve this goal, a Christian teacher who is full of creativity is needed. This study uses qualitative methods and produces descriptive data. The basis for choosing this pattern is an attempt to describe the survey object in detail. The key tool in this research is the researcher, then the research informants are parents, students, lecturers, Christian leaders and church pastors. The object of research is a Christian religion teacher. Data collection techniques are observation, document review, and noun class or triangulation. Data examination was carried out according to the theory of Miles and colleagues. The conclusion of the study is that Christian religious teachers are obliged to continuously improve learning creativity. Efforts that can be made include: needing to understand the various factors that influence the increase in learning creativity, mastering and maximizing all basic teaching skills, practicing and preparing for teaching, being able to do classroom management, understanding the use of various methods, strategies and learning models, understanding technology and educational media, understand research principles and be able to interpret the results. AbstrakGuru agama Kristen harus memiliki keterampilan aptitude dan non aptitude serta kreativitas pembelajaran yang baik. Guru agama Kristen dalam tugasnya berkewajiban menata, membimbing, menuntun dan mewujudkan alam belajar yang sehat dan menyenangkan bagi peserta didik. Termasuk melakukan pembinaan, membentuk dan membantu peserta didik mencapai prestasi belajarnya. Untuk mencapai maksud tersebut, dibutuhkan guru agama Kristen yang penuh kreasi. Penelitian ini menggunakan metode kualitatif dan melahirkan data deskriptif. Dasar memilih pola ini, yaitu upaya mendeskripsikan objek survei dengan detail. Alat kunci dalam penelitian ini adalah peneliti, kemudian informan penelitian adalah orangtua, mahasiswa, dosen, pemimpin Kristen dan pendeta jemaat. Objek penelitian adalah guru agama Kristen. Teknik pengumpulan data adalah pengamatan, kajian dokumen, dan kelas nomina atau triangulasi. Pemeriksaan data dilakukan menurut teori Miles dan kawan-kawan. Kesimpulan penelitian bahwa guru agama Kristen wajib melakukan peningkatan kreativitas pembelajaran secara kontinyu. Upaya-upaya yang dapat dilakukan antara lain: perlu memahami berbagai faktor yang mempengaruhi peningkatan kreativitas pembelajaran, menguasai dan memaksimalkan keseluruhan keterampilan dasar mengajar, melakukan praktek dan persiapan mengajar, mampu melakukan manajerial kelas, memahami penggunaan berbagai metode, strategi dan model pembelajaran, memahami teknologi dan media pendidikan, memahami prinsip-prinsip penelitian dan mampu menafsirkan hasilnya.